Well-Being support by Sandwich generation in the Films Cinta Pertama, Kedua, dan Ketiga - Sudarji, Shanty; Marta, Rustono Farady; Panggabean, Hana; Jatmika, Devi (International Journal of Communication and Society, 2023)
Large families are very common in Indonesian culture. Individuals living in extended families with multigenerational childcare responsibilities are known as the Sandwich Generation. The challenges involved in multi-generational parenting impact the lifestyle of the Sandwich Generation as a whole, including personal time, career development, and financial stability. The Sandwich Generation is at risk for various mental health problems, including stress, depression, and anxiety, due to increased pressure and demands. The objective of this research is to see the picture of well-being support in the sandwich generation as reflected in the films Cinta Pertama, Kedua, dan Ketiga. The research method used to review the films Cinta Pertama, Kedua, dan Ketiga is Content Analysis by Philip Mayring with an interpretive paradigm. Abstraction, explication, and arrangement were carried out to analyze this film. There are three things that can be concluded from the content analysis of the films Cinta Pertama, Kedua, dan Ketiga. First, the dynamics of the life of the sandwich generation are described as full of problems. Second, the main character Dewa is described as having well-being support from his family. Third, the well-being support obtained cannot be separated from the standard culture that exists in Indonesia, namely Guyub, where people live in harmony and support each other as a family member.